2018
DOI: 10.21037/jtd.2018.04.75
|View full text |Cite
|
Sign up to set email alerts
|

It is safe and feasible to omit the chest tube postoperatively for selected patients receiving thoracoscopic pulmonary resection: a meta-analysis

Abstract: This meta-analysis conforms that it is feasible and safe to omit chest tube after thoracoscopic pulmonary resection for patients carefully selected. Randomized controlled trails (RCTs) are urgently needed to verify this conclusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…9 Interestingly, there is also evidence suggesting the safety of avoiding any chest drain in selected patients undergoing minimally invasive surgery, showing better pain control and no difference in 30-day morbidity. 10…”
Section: Discussionmentioning
confidence: 99%
“…9 Interestingly, there is also evidence suggesting the safety of avoiding any chest drain in selected patients undergoing minimally invasive surgery, showing better pain control and no difference in 30-day morbidity. 10…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of nine studies, including 918 patients undergoing pulmonary resection by VATS, found that approximately 50% of patients did not have a chest tube inserted. In these patients, postoperative pain scores and LOS were significantly reduced, compared with patients who had a chest tube inserted, with no difference in 30-day morbidity or re-intervention rates between the two groups (Li et al 2018 ). These findings suggest that omitting the chest tube is safe and feasible in selected patients.…”
Section: Postoperative Carementioning
confidence: 99%
“…However, high-level evidence from randomised controlled trials is scarce. One systematic review (18) published in 2010 including one randomized controlled trial (RCT) (19) and three observational studies (20)(21)(22), and another with meta-analysis (23) of nine observational studies (20,(24)(25)(26)(27)(28)(29)(30)(31) was published in 2018. Subsequently, additional three RCTs (32)(33)(34) and six observational studies (35)(36)(37)(38)(39)(40) were published.…”
Section: Introductionmentioning
confidence: 99%